Embracing technology in the workplace: evaluating employee adoption of the mobile application for restaurant search and reservations (MARSR) - Abdul Aziz, Azdel; Zainol, Amir Azahari; Ahmad, Noor Azmi; Abdul Karim, Kamril Juraidi (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2025)
The study of employees’ technology acceptance such as the Mobile Application for Restaurant Search and Reservation (MARSR) system has not been widely researched on. The study examines factors influencing restaurant employees' intention to use the MARSR system in Klang Valley hotel restaurants. Using the Unified Theory of Acceptance and Use of Technology (UTAUT), data from 132 respondents reveals that facilitating conditions significantly impact employee intention to use MARSR. Performance expectancy and social influence also influence acceptance, while effort expectancy does not. These findings can help restaurant and hotel managers increase MARSR system adoption among employees, enhancing productivity and customer experience.